Enhancing Elementary Students’ Mathematical Problem-Solving Skills Through AI-Assisted Problem-Based Learning - Noviyana, Hesti; Rahmawati, Fitriana; Rara Kirana, Arinta; Jessy Tanod, Mareyke (Journal of Integrated Elementary Education, 2025)
The purpose of this study was to investigate the effectiveness of the use of AI assisted PBL on enhancing elementary school students' mathematical problem-solving skills. Inspired by the persisting issues in developing skills of elementary school students in Indonesian, this study investigated whether AI-supported PBL might be more a promising method of instruction than traditional teaching method. Quasi-experimental with non-equivalent control group design was applied with 5th graders (N = 60). The experimental group was taught using AI-assisted PBL, and the control group was taught by traditional method. An established test based on Polya's heuristic devised was used to collect data. Descriptive statistics, independent samples t-test, and N-Gain analysis were used to analyze the data. The results showed a significant difference (p < 0.05) in the two groups with respect to all indicators (comprehending the problem, formulating a plan, executing the plan and evaluating the solution); for the experimental group (M = 78.40; SD = 7.20) exceeded the control groups (M = 68.10; SD = 8.50). In addition, the treatment group exhibited a high N-Gain score (M= 0.78). The findings suggest that using AI-assisted PBL is an effective way to promote elementary students’ mathematical problem-solving ability, which indicates the role of integrating modern technology with creative pedagogical pattern in math teaching.